The effect of the MNB's communication on financial markets - Péter Gábriel; Klára Pintér (Magyar Nemzeti Bank, 2006)
Our paper aims to assess how the Magyar Nemzeti Bank's communication affects financial asset prices. We find that the central bank plays the most important role in influencing long-term yields. The effect on the exchange rate is less pronounced, while short-term yields are influenced only by the communication related to the exchange rate. Analysing the direction and channels of communication we observe two asymmetries. The central bank is more successful in signalling monetary policy tightening than easing and with the increase of time horizon the written communication gains in importance and dominates the verbal forms.
Keywords: C22; E43; E52; 330; communication; transmission mechanism; Zentralbank; Kommunikation; Ankündigungseffekt; Rendite; Wechselkurs; Schätzung; Ungarn